Photonic crystal fiber drug sensor based on surface plasmon resonance - Sally K. Abbas; Soudad S. Ahmed (Iraqi Journal of Laser, 2024)
This study introduces a sensor using Photonic Crystal Fiber (PCF) and Surface Plasmon Resonance (SPR) technology. Gold (Au) was applied as a thin coating on a PCF, which had been previously coated with a chemically stable gold compound that exhibits plasmonic properties. The thickness of the gold coating was 40nm. The performance metrics, such as sensitivity (including wavelength sensitivity and amplitude sensitivity) and resolution, were assessed by simulation via the COMSOL program. The suggested sensor was developed utilizing the finite element method and then subjected to numerical analysis. The findings indicate that the surface of Photonic Crystal Fiber when coated with Au, functions as a sensor for detecting the refractive index (IR) of expired pharmaceutical samples. Research is conducted on the effects of the structural parameters on the resonant spectra with the aim of enhancing sensing performance. The highest amplitude sensitivity recorded was 31.2 RIU-1, whereas the maximum resolution reached was 6×10-5 RIU. These measurements were obtained within the detection range of 1.383 to 1.399.